2022
DOI: 10.3390/ma15103442
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Process Design for Asymmetric Single-Point Incremental Forming of Individual Titanium Alloy Hip Cup Prosthesis

Abstract: Advanced manufacturing techniques aimed at implants with high dependability, flexibility, and low manufacturing costs are crucial in meeting the growing demand for high-quality products such as biomedical implants. Incremental sheet forming is a promising flexible manufacturing approach for rapidly prototyping sheet metal components using low-cost tools. Titanium and its alloys are used to shape most biomedical implants because of their superior mechanical qualities, biocompatibility, low weight, and great str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Li et al [34] investigated the tool path optimisation of induction heating-assisted SPIF using machine learning. Material formability and surface quality were improved following the optimisation of the tool path and using machine learning; however, noticeable oxidation and alpha layer of the sheet material at heating temperature ~1040 • C were reported, and they were eliminated at ~950 • C. Frikha et al [35] explored incremental forming of grade 2 α titanium for biomedical application (hip cup prostheses). The research suggested a novel multistep process in which a deep drawing was used for the spherical cup part, whereas incremental forming was used for the outer flange part.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [34] investigated the tool path optimisation of induction heating-assisted SPIF using machine learning. Material formability and surface quality were improved following the optimisation of the tool path and using machine learning; however, noticeable oxidation and alpha layer of the sheet material at heating temperature ~1040 • C were reported, and they were eliminated at ~950 • C. Frikha et al [35] explored incremental forming of grade 2 α titanium for biomedical application (hip cup prostheses). The research suggested a novel multistep process in which a deep drawing was used for the spherical cup part, whereas incremental forming was used for the outer flange part.…”
Section: Introductionmentioning
confidence: 99%